2011
DOI: 10.1094/mpmi-10-10-0246
|View full text |Cite
|
Sign up to set email alerts
|

The Helper Component Proteinase Cistron of Potato virus Y Induces Hypersensitivity and Resistance in Potato Genotypes Carrying Dominant Resistance Genes on Chromosome IV

Abstract: The Nc(tbr) and Ny(tbr) genes in Solanum tuberosum determine hypersensitive reactions, characterized by necrotic reactions and restriction of the virus systemic movement, toward isolates belonging to clade C and clade O of Potato virus Y (PVY), respectively. We describe a new resistance from S. sparsipilum which possesses the same phenotype and specificity as Nc(tbr) and is controlled by a dominant gene designated Nc(spl). Nc(spl) maps on potato chromosome IV close or allelic to Ny(tbr). The helper component p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…Our data are consistent with recent findings that concurrent mutations of HC-Pro and P3 are required for G2 (the N isolate) to gain virulence on Rsv1 -genotype soybean [31], [43]. The HC-Pro of Potato virus Y (PVY) has been shown to act as a virulence determinant on potato ( Solanum tuberosum ) and S. sparsipilum containing PVY resistance genes Nc tbr and Nc spl , respectively [2]. In several other studies, HC-Pro was found to be involved in potyvirus symptom development [44][48].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data are consistent with recent findings that concurrent mutations of HC-Pro and P3 are required for G2 (the N isolate) to gain virulence on Rsv1 -genotype soybean [31], [43]. The HC-Pro of Potato virus Y (PVY) has been shown to act as a virulence determinant on potato ( Solanum tuberosum ) and S. sparsipilum containing PVY resistance genes Nc tbr and Nc spl , respectively [2]. In several other studies, HC-Pro was found to be involved in potyvirus symptom development [44][48].…”
Section: Discussionsupporting
confidence: 92%
“…The use of genetic resistance is considered the most effective and sustainable approach to the control of plant pathogens as it is environmentally-friendly and target-specific, and provides reliable protection without additional labor or material costs during the growing season [2], [3]. The major genetic resistance that has been extensively used in agriculture is mediated by R gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. tuberosum ssp andigena also was a source of a dominant HR gene for resistance to PVA (Ra adg ), as well as a source of a recessive resistance (ra) to systemic movement of PVA; both of these genes were linked to Ry adg on chromosome XI (Hämäläinen et al, 2000). Genes encoding an HR to PVY in potato (Ny tbr ) and in S. sparsipilum (Nc spl ) were found to be either allelic or map very close on chromosome IV (Moury et al, 2011).…”
Section: Potyvirusesmentioning
confidence: 99%
“…For example, PVY VPg interacts with a recessive resistance protein, pvr2 in pepper which is also known as a member of eukaryotic initiation factor 4E (elF4E) [9]. Another PVY viral protein, HC-Pro is known to function broadly in potato and tobacco by interacting with elF4E and its elFiso4E [10], and is also involved in HR-like cell death in potato by responding to resistance genes called NC tbr , NC spl and Ny tbr [7]. A PVY protease, NIa protease (also called NIaPro) was found to be required for Ry -mediated resistance of potato against PVY [5].…”
Section: Introductionmentioning
confidence: 99%